2019
DOI: 10.21873/cgp.20144
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Fusion Transcripts in Undifferentiated Pleomorphic Sarcomas by Transcriptome Sequencing

Abstract: Background/Aim: Undifferentiated pleomorphic sarcoma (UPS) is an aggressive mesenchymal neoplasm characterized by chromosomal instability. The aim of this study was to identify fusion events involved in UPS. Materials and Methods: Transcriptome sequencing was performed to search for new fusion genes in 19 UPS samples, including two paired recurrent (R) and re-recurrent (RR) samples. Results: A total of 66 fusion genes were detected. Among them, 10 novel fusion genes were further confirmed by reverse transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This research helped us to understand the molecular characteristics of UPS more deeply, and given us a certain understanding of UPS chemotherapy resistance. In addition, some new fusion genes including PDGFRA-MACROD2, NCOR1-MAP2K1 were found in Zheng’s research, which provided an important clue for targeted therapy 31. As for adjuvant radiotherapy, Belal9 reported that adjuvant radiotherapy was related to a decreased risk of local recurrence and Hsu17 showed it could improve local control, while our data showed no benefit in prolong overall survival time, local recurrence time and metastasis time.…”
Section: Discussionmentioning
confidence: 54%
“…This research helped us to understand the molecular characteristics of UPS more deeply, and given us a certain understanding of UPS chemotherapy resistance. In addition, some new fusion genes including PDGFRA-MACROD2, NCOR1-MAP2K1 were found in Zheng’s research, which provided an important clue for targeted therapy 31. As for adjuvant radiotherapy, Belal9 reported that adjuvant radiotherapy was related to a decreased risk of local recurrence and Hsu17 showed it could improve local control, while our data showed no benefit in prolong overall survival time, local recurrence time and metastasis time.…”
Section: Discussionmentioning
confidence: 54%
“…A specific recurring deletion of exon 6 has been observed in esophageal squamous cell carcinoma and gastric cancer [98]. For MACROD1, a RUNX-MACROD1 fusion was identified in leukaemia [99] and, for MACROD2, a PDGFRA-MACROD2 fusion in a pleomorphic sarcoma [100]. Despite the low number of identified mutations in patient tumour samples, several reports have correlated MACROD1 or MACROD2 expression levels with the clinical outcome, as described in the next paragraphs.…”
Section: Mono(adp-ribosyl)ation In Cancermentioning
confidence: 99%
“…According to data from the Surveillance, Epidemiology, and End Results (SEER) program, UPS comprises 17.1% of cases of STSs (2). The mainstay of treatment for UPS is surgical resection with adequate margins, with consideration given to perioperative RT and chemotherapy (3,4). UPS is notorious for a high rate of recurrence with high metastatic potential, making the management of UPS difficult, and the prognosis is poor for patients Frontiers in Oncology frontiersin.org 01…”
mentioning
confidence: 99%
“…with metastatic or surgically unresectable disease (4). Here, we present a patient with UPS involving the chest wall who received treatment with ICIs prior to the diagnosis of UPS.…”
mentioning
confidence: 99%